1988
DOI: 10.3146/i0095-3679-15-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Metolachlor Effects on Peanut Growth and Development

Abstract: Growth and yield responses of peanuts (Arachis hypogaea L.) to preplant incorporated applications of metolachlor [2chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-l-methylethyl)acetamide] herbicide were studied at two locations in Georgia. At Sycamore, GK-7 peanuts which received 3.8 cm irrigation immediately following herbicide incorporation and planting were generally stunted and yielded less than non-inigated peanuts. Metolachlor rates from 2.2 to 6.7 kg ai/ha reduced early and late season growth of irrigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 5 publications
10
57
1
Order By: Relevance
“…Visible injury from metolachlor does not always result in lower peanut yield compared with yield of non-treated peanut under weed-free conditions when applied at rates recommended in by the manufacturer (Cardina and Swann, 1988;Clewis et al, 2007;Grichar and Dotray, 2012). In a study similar to the one reported in this article, Grichar et al (2015) observed in Texas that peanut yield and market grade characteristics were not affected by acetochlor rate or application timing (PPI, PRE, EPOST, POST).…”
Section: Peanut Tolerancesupporting
confidence: 66%
See 3 more Smart Citations
“…Visible injury from metolachlor does not always result in lower peanut yield compared with yield of non-treated peanut under weed-free conditions when applied at rates recommended in by the manufacturer (Cardina and Swann, 1988;Clewis et al, 2007;Grichar and Dotray, 2012). In a study similar to the one reported in this article, Grichar et al (2015) observed in Texas that peanut yield and market grade characteristics were not affected by acetochlor rate or application timing (PPI, PRE, EPOST, POST).…”
Section: Peanut Tolerancesupporting
confidence: 66%
“…Peanut stunting and delayed emergence with Smetolachlor has been noted in previous studies (Cardina and Swann, 1988;Clewis et al, 2007;Grichar and Dotray, 2012). Grichar and Dotray (2012) reported peanut stunting from 0 to 15% with S-metolachlor alone and in combination with paraquat, and stunting increased as application timing was delayed to 28 d compared to 7 d after peanut cracking.…”
Section: Peanut Is a Valuable Commodity In The Unitedmentioning
confidence: 93%
See 2 more Smart Citations
“…They also reported that POST applications of metolachlor followed by irrigation within 24 h could be effective for yellow nutsedge (Cyperus esculentus L.) control and reduce the chance of peanut injury from soil applications of metolachlor. Combinations of factors, such as herbicide rate, moisture conditions at planting, soil organic matter, and pH may affect peanut injury by chloroacetamide herbicides, such as acetochlor and S-metolachlor (Cardina and Swann, 1988;Mueller et al, 1999;Osborne et al, 1995;Wehtje et al, 1988). Cardina and Swann (1988) reported that metolachlor often delayed peanut emergence and reduced peanut growth when irrigation followed planting.…”
Section: Resultsmentioning
confidence: 99%